\(\displaystyle r=[1+i/12]^{12}-1\)

1. Add 1 to both sides

\(\displaystyle r+1=[1+i/12]^{12}\)

2. Open the brackets so that

\(\displaystyle r+1=1+i^{12}/12^{12}\)

3. Then multiply both sides by \(\displaystyle 12^{12}\) to give

\(\displaystyle 12^{12}(r+1)=1+i^{12}\)

4. And then finally

\(\displaystyle 12^{1/12}(r+1)-1=i\)

The answer in the book though is

\(\displaystyle 12((r+1)^{1/12})-1=i\)

But I don't understand why I was supposed raise\(\displaystyle (r+1)\) to the power of 12 when I multiplied by \(\displaystyle 12^{12}\) in step 3